Intelligent Management of Air Traffic Flow Based on Intelligent Motion Coordinate Data Model - Junhao Liu; Qing Cheng; Yuanji Wang; Changqi Yang; Rui Zhou; Xinping Zhu; Di Yao; Junjie Zhou; Yaqian Du; Shanshan Yang (Journal of Advanced Transportation)
To adapt to the intelligent management of traffic flow in modern aviation, this study improves the algorithm according to the data exercise method and establishes the mathematical model and vector model of intelligent motion coordinates. Moreover, according to the simulation test method, this study analyzes the six-degree-of-freedom equation of motion in the coordinate system of the civil aviation aircraft and uses the simulation method to regard the civil aviation as a rigid body with a certain mass and mass distribution. In addition, this study builds an intelligent model based on the demand analysis, and according to the actual demand, this study combines the simulation method to analyze the structure of the intelligent management model of air traffic flow. Finally, this study uses the experimental analysis method to verify the effect of the model proposed in this study and combines the experimental research to verify that the model proposed in this study has a certain effect.